(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A girl’s good healthy adolescent growth and development helps her prepare for healthy pregnancies during her reproductive years. Females who stay in school are more likely to put off getting married and having children at an early stage. For teenagers under the age of 18, and especially for those under 15, an early pregnancy might have catastrophic repercussions. Teenage girls and their unborn children have a substantially increased risk of problems and fatalities. In order to protect their health and wellbeing, adolescents should postpone marriage and pregnancy, which can be accomplished with the aid of health professionals and community outreach programmes. Ensuring pregnancies at an appropriate reproductive age, taking into account the physical and mental fitness, will contribute towards reducing the maternal and infant mortality rates, both of which contribute towards various indices, that help determine our countries overall holistic growth and development.